A dynamical model of echinococcosis with optimal control and cost-effectiveness. (December 2021) - Zhao, Jianglin; Yang, Run
Abstract: A dynamical model of echinococcosis transmission with optimal control strategies is first presented. The basic reproduction number of the model is determined and employed to study the global stability of the disease-free and endemic equilibrium points. The optimal control problem is formulated and solved analytically. Numerical simulations show that optimal control strategies could effectively reduce the transmission of echinococcosis. The cost-effectiveness analysis suggests that a combination of health education, anthelmintic treatment, and home slaughter inspection could provide the best cost-effective strategy to control the transmission of echinococcosis. Furthermore, it finds that anthelmintic treatment and environmental disinfection may shorten the time of eliminating the disease. The results may be helpful for prevention and control of echinococcosis in Ganzi Tibetan Autonomous Prefecture, China and other areas of echinococcosis.